Predicting role of social support and academic stress on life satisfaction among Malaysian adolescents - Yaacob, Siti Nor; Foo, Sophia Mei Yee; Gan, Su Wan (Penerbit UTM Press, 2017)
This paper aimed to examine the predicting role of social support (family and friends) and academic stress on life satisfaction among adolescents in Malaysia. A total of 359 secondary school students (mean of age= 16.26; 133 male adolescents, 37.0%) in Selangor were selected with cluster sampling method. Self-administrated questionnaires with existing established measurements were used for collecting response. Prior to conducting regression analysis, Pearson correlation analysis was ran for testing the relationship between social support (family and friends), academic stress and life satisfaction. Results showed that both social support from family (r = .433, p < .01) and social support from friends (r = .483, p < .01) had significant positive relationship with life satisfaction. On the other hand, academic stress (r = -.011, p > .05) was failed to significantly related to life satisfaction. Thus, only social support from friends and family were included in regression analysis. By controlled respondents’ background, social support from friends (β = 0.382, p < 0.001) and social support from family (β = 0.297, p < 0.001) were found to be the predictors of adolescents’ life satisfaction. By interpreting the unstandardized beta values, social support from friends contributed higher predicting effect on adolescents’ life satisfaction as compared with social support from family. In order to increase life satisfaction among adolescents, intervention should focus on the social support that provided by both family members and friends.